Provenance and paleogeography of the Jurassic Northwestern Qaidam Basin (NW China): Evidence from sedimentary records and detrital zircon geochronology. (1st April 2020) - Zhao, Junfeng; Zeng, Xu; Tian, Jixian; Hu, Chao; Wang, Di; Yan, Zhandong; Wang, Ke; Zhao, Xudong
Graphical abstract: Paleogeography reconstruction of the northwestern Qaidam Basin in Jurassic. (A) Early Jurassic, (B) Middle Jurassic, (C) Late Jurassic. Highlights: Sediment in J1 mainly originated from the Altyn Mts. and inner-basin paleo-uplifts. Sediment in J2 was mainly from the South Qilian Mts. with minor from UHP belts. The inner Qaidam–Saishiteng Mts.–Suganhu area belonged to one basin in J2 . Several rift basins developed in J1 then a larger depression basin developed in J2 . The interaction of the adjacent plates' subduction led to subsidence in J1-2 . Abstract: The Qaidam Basin is the largest Meso–Cenozoic petroliferous basin on the northeastern Tibetan Plateau and was situated at the northern margin of the Eastern Tethys during the Mesozoic. Jurassic strata are the main source rocks and reservoirs in the northern and western segments of this basin. However, due to exceptionally thick overlying Cenozoic strata, intensive post-depositional modification and limited deep exploration data, several crucial problems regarding this basin remain controversial, including provenance supply, original sedimentary extent, and overall properties in the Jurassic period. This hinders further understanding of regional geological evolution and hydrocarbon exploration. This paper focuses on comparison of residual Jurassic strata in the northwestern Qaidam Basin, the adjacent Saishiteng Mountains and the Suganhu area to the north based on sedimentology and provenance analyses. Detrital zircon geochronology was employed to examine the provenance of Jurassic sediments in different areas and to reconstruct their dispersal patterns. Results show that the Lower Jurassic deposits are characterized by near provenance and rapid facies shift. Fan deltas, braided river deltas, and lacustrine deposits are commonly developed. The Lower Jurassic source area was mainly located in the south Altyn Tagh Mountains. Sedimentary extent and depocenters in the Middle and Late Jurassic transferred northwards to the current piedmont of the Saishiteng and South Qilian mountains. The residual Jurassic in the Saishiteng Mountains is similar and comparable with coeval strata in the Suganhu area as well as the inner Qaidam Basin. Detrital zircon ages indicate multiple provenances in the Middle Jurassic, of which the southern Qilian Mountains are the most important. In the Middle Jurassic, deposition occurred across large areas of the Saishiteng Mountains which belonged to the same basin as the inner Qaidam Basin and the Suganhu areas. A series of small-scale continental rift basins developed in the western part of northwestern Qaidam in the Early Jurassic and then developed into a larger depression from the late Early Jurassic to the Late Jurassic. Post-collision extension was conducive to the development of rift basins in the Early Jurassic. Subduction of the northern Mongolian–Okhotsk and southern Central Tethys Ocean interactively led to an extensional tectonic setting and the development of a depression basin in late Early to Middle Jurassic. The continuous northward compression of the Qiangtang Block mainly resulted in a compressive tectonic setting in the Late Jurassic.